Teaching Sustainability in Qatar: Challenges for Teacher Readiness - Jennifer Bruder (323066) (2025)
The core obstacle in imparting knowledge about sustainability lies in teachers’ readiness, which encompasses an internal motivation and commitment towards sustainability, adequate knowledge, and teaching techniques, as well as an educational setting that fosters and maintains the incorporation of sustainability within the local cultural context. This chapter explains teacher readiness and explores salient challenges to teacher readiness within Qatar. Notable challenges include inadequate teacher education, professional readiness, educational borrowing, cultural influences, teachers’ attitudes, and school culture. The chapter offers a range of localised recommendations based on research findings. Providing teachers with sufficient and specific ESD and GCED training can result in favourable outcomes regarding their attitudes, experiences, and confidence towards teaching sustainability. Other Information Published in: Gulf Studies License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/978-981-97-9667-0_2